MIB-1 labelling index is an independent prognostic marker in primary breast cancer. - Jansen, R. L. (Nature Publishing Group|1, 1998)
The proliferative activity of a tumour is considered to be an important prognostic factor in primary breast cancer. We have investigated the prognostic value of the MIB-1 labelling index in 341 patients with primary breast cancer and compared the results with the S-phase fraction in 220 patients of the same cohort. All patients were treated in one hospital and had a median follow-up of 128 months. No correlation between MIB-1 labelling and S-phase fraction could be demonstrated. MIB-1 had prognostic value for disease-free survival in the whole group of patients (P < 0.001) and in the node-negative subgroup (P < 0.001). In multivariate analysis, MIB-1 was an independent prognostic factor (P = 0.004) besides axillary lymph node status (P = 0.001). In univariate analysis high S-phase fraction was associated with decreased overall survival (P = 0.04); however, not in multivariate analysis. Moreover, S-phase fraction had a borderline prognostic significance for post-relapse survival in multivariate analysis (P= 0.08). Thus, in conclusion, the growth fraction of a tumour as determined by the MIB-1 labelling index is an important prognostic factor in patients with primary breast cancer.